Legal Framework Governing Foreign Property Ownership in Indonesia’s Special Economic Zones - Elsi Kartika Sari; Ninuk Wijiningsih; Ahmad Sabirin (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the tension between the principle of nationality in the Basic Agrarian Law (UUPA) which limits the ownership of land rights to Indonesian citizens and the new policy providing access to property ownership for foreign nationals in Special Economic Zones (SEZs) through the Job Creation Law, Government Regulation Number 18 of 2021, and Decree of the Minister of ATR/BPN Number 1241 of 2022. Even though various studies have discussed the regulation of property ownership by foreign nationals, few studies analyse the constitutional implications and normative consequences of extending rights on the basis of nationality as the foundation of Indonesian agrarian law. Normative legal methods are used through legislative and conceptual approaches, with qualitative analysis of primary and secondary materials. The novelty of this study lies in the use of Progressive Law theory, combined with the perspectives of legal certainty and constitutional identity, to interpret the relationship between the UUPA and the post-Job Creation Law regulations. Furthermore, expanding access to property ownership for foreign nationals does not necessarily alter the principle of nationality; rather, it represents a limited reinterpretation to support investment and economic development goals. The results show that the current regulations allow foreign nationals to own landed houses and flats in SEZs, subject to certain requirements, such as minimum price limits, land area, ownership limits, and legal immigration status. However, various limitations remain in place, including restrictions on the type of land rights, location of ownership, and surveillance mechanisms to prevent speculation and safeguard state sovereignty. In this context, regulatory harmonisation is needed to ensure legal certainty while maintaining Indonesia's constitutional identity in agrarian governance amid the demands of global investment liberalisation.